(untitled) (Annals of Medical Research, 2021)
Aim: The present study aimed to evaluate the potential role of intra-aortic balloon pump (IABP)-related thrombocytopenia in patients with cardiogenic shock (CS) due to ST elevation myocardial infarction (STEMI) dien in hospital.Material and Methods: We retrospectively included 142 consecutive CS patients who were treated with IABP support from September 2013 to March 2017 in a tertiary heart center. IABP-related thrombocytopenia was defined as a platelet count of 150.000 mm3 or a 50% or greater reduction in the platelet count from the baseline following the IABP’s insertion. In-hospital, all-cause mortality was the primary endpoint.Results: The incidence rate of thrombocytopenia was 19% (n=27 patients). In-hospital mortality was significantly higher in patients who experienced thrombocytopenia compared to those who did not [22 patients (81.5%) vs. 56 patients (48.7%), respectively; p=0.004]. In a multivariate analysis, a decline in platelet count (OR: 1.037, 95%; CI: 1.011–1.064; p=0.005) was found to be independently associated with in-hospital mortality. In a receiver operating characteristic curve analysis, the optimal cut-off value of the decline in platelet count for the prediction of in-hospital mortality was ≥ 18.2%, with a sensitivity of 60% and a specificity of 77% [area under curve (AUC): 0.70, 95%; CI:0.61–0.78; p0.001].Conclusion: In the present study, we observed that the development of thrombocytopenia during IABP support was independently associated with in-hospital mortality in CS patients.Keywords: Intra-aortic balloon pump; thrombocytopenia; cardiogenic shock; in-hospital mortality.